Lipid rafts function in biosynthetic delivery of proteins to the cell surface in yeast - Bagnat, Michel (The National Academy of Sciences, 2000)
Lipid rafts, formed by lateral association of sphingolipids and cholesterol, have been implicated in membrane traffic and cell signaling in mammalian cells. Sphingolipids also have been shown to play a role in protein sorting in yeast. Therefore, we wanted to investigate whether lipid rafts exist in yeast and whether these membrane microdomains have an analogous function to their mammalian counterparts. We first developed a protocol for isolating detergent-insoluble glycolipid-enriched complexes (DIGs) from yeast cells. Sequencing of the major protein components of the isolated DIGs by mass spectrometry allowed us to identify, among others, Gas1p, Pma1p, and Nce2p. Using lipid biosynthetic mutants we could demonstrate that conditions that impair the synthesis of sphingolipids and ergosterol also disrupt raft association of Gas1p and Pma1p but not the secretion of acid phosphatase. That endoplasmic reticulum (ER)-to-Golgi transport of Gas1p is blocked in the sphingolipid mutant lcb1–100 raised the question of whether proteins associate with lipid rafts in the ER or later as shown in mammalian cells. Using the sec18–1 mutant we found that DIGs are present already in the ER. Taken together, our results suggest that lipid rafts are involved in the biosynthetic delivery of proteins to the yeast plasma membrane.